Dentition state of inhabitants of Kraków (XI–XVIIIc.). Dental caries - Gleń, Elżbieta (Anthropological Review, 1975)
On 213 skulls dated at XI - XVIII c. originating from Kraków and its vicinity occurence of dental caries was analysed. Rapid increase in frequency of this pathological process together with progress of civilisation was found. Changed life conditions created new etiological factors determinig occurence of caries. Localization of carious cavities is related to the said changes. In medieval skulls cavitics most frequently were observed near collum and on contact surfaces of tooth. On these places were Food conditions for fermentation of deposited food debris. Products of the fermentation penetrate into enamel and contribute to the decay of tooth hard tissues. On occlusal surfaces conditions for development of carious cavities were considerably worse, because these surfaces have been smoothed up quickly by attrition resulting from intense chewing. Another situation was found in modern series where attrition was less intense and as a result more cavities were present on occlusal surfaces. No differences in intensity of caries occurence were found between right and left side of dental arches, but it is noteworthy that upper dental arch was more frequently attacked. Problems of sex and age differences in carious involvement require further studies.